Tris(4‐chlorophenyl)methane and tris(4‐chlorophenyl)methanol disrupt pancreatic organogenesis and gene expression in zebrafish embryos. Issue 4 (5th December 2022) - Wilson, Peyton W.; Cho, Christine; Allsing, Nicholas; Khanum, Saleha; Bose, Pria; Grubschmidt, Ava; Sant, Karilyn E.
Abstract: Objectives: Tris(4‐chlorophenyl) methane (TCPM) and tris(4‐chlorophenyl)methanol (TCPMOH) are anthropogenic environmental contaminants believed to be manufacturing byproducts of the organochlorine pesticide dichlorodiphenyltrichloroethane (DDT) due to environmental co‐occurrence. TCPM and TCPMOH are persistent, bioaccumulate in the environment, and are detected in human breast milk and adipose tissues. DDT exposures have been previously shown to disrupt insulin signaling and glucoregulation, increasing risk for diabetes. We have previously shown that embryonic exposures organochlorines such as polychlorinated biphenyls disrupted pancreatic development and early embryonic glucoregulatory networks. Here, we determined the impacts of the similar compounds TCPM and TCPMOH on zebrafish pancreatic growth and gene expression following developmental exposures. Methods: Zebrafish embryos were exposed to 50 nM TCPM or TCPMOH beginning at 24 hr postfertilization (hpf) and exposures were refreshed daily. At 96 hpf, pancreatic growth and islet area were directly visualized in Tg ( ptf1a :: GFP ) and Tg ( insulin :: GFP ) embryos, respectively, using microscopy. Gene expression was assessed at 100 hpf with RNA sequencing. Results: Islet and total pancreas area were reduced by 20.8% and 13% in embryos exposed to 50 nM TCPMOH compared to controls. TCPM did not induce significant morphological changes to the developing pancreas, indicating TCPMOH, but not TCPM, impairs pancreatic development despite similarity in molecular responses. Transcriptomic responses to TCPM and TCPMOH were correlated ( R 2 = .903), and pathway analysis found downregulation of processes including retinol metabolism, circadian rhythm, and steroid biosynthesis. Conclusion: Overall, our data suggest that TCPM and TCPMOH may be hazardous to embryonic growth and development.